การตรวจหาแกมีโตไซต์ของพลาสโมเดียม ไวแวกซ์ ในกระแสเลือด โดยวิธีปฏิกิริยาลูกโซ่โพลีเมอร์เรส รีเวอร์ส ทรานสคริปชั่น - นภาพร กวมทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Malaria remains one of the world’s most important public health burdens. It has been estimated that 350-500 million people are infected with malaria, resulting in about 1 million deaths each year. Although malaria caused by Plasmodium falciparum is the most pernicious and contributes the most disease burden of all malaria species at the global scale, Plasmodium vivax occupies a larger geographical niche and is capable of causing chronic relapsing illness due to the presence of a dormant stage in hepatocyte and can be responsible for severe clinical syndromes. For malaria eradication aiming at abrogating malaria transmission, circulating gametocytes in infected individuals are targets for drugs and vaccines. Therefore, estimation of gametocyte carriage has important implication for disease control. Although microscopy is considered to be a practical tool for malaria diagnosis. Furthermore, a number of infected blood samples harboring parasites below microscopic detection threshold are undiagnosed by microscopy. Herein, a novel nested reverse transcription polymerase chain reaction (nested RT-PCR) targeting Pvs25 mRNA was developed for detection of mature gametocytes (stage V) of P. vivax. The performance of the RT-PCR method was evaluated using blood samples from 106 P. vivax-infected patients who attended a malaria clinic in Tak Province in rainy season (n=49) and in dry season (n=57). RNA was extracted from both fresh blood spotted onto filter paper and RNA-preserved blood sample from each subject. Results showed that 56% (28/50) and 52.38% (22/42) of patients infected with P. vivax collected in dry and in rainy seasons, respectively, had gametocytes in their circulation based on microscopic examination of Giemsa stained thin and thick blood films. On the other hand, the nested RT-PCR method could specifically amplify Pvs25 mRNA in 91.84% (45/49) and 94.87% (37/39) of RNA-preserved blood samples from patients infected with P. vivax in dry and in rainy seasons, respectively. In total, 93.18% (82/88) of RNA-preserved blood samples gave positive tests for nested RT-PCR method and 89.77% (79/88) of blood samples spotted onto filter paper conferred positive results. It is noteworthy that no significant difference in diagnostic sensitivity for Pvs25 mRNA detection by nested RT-PCR was observed when templates were derived from RNA-preserved blood samples or from blood samples spotted onto filter paper (p>0.05). The prevalence of P. vivax gametocyte carriage did not show significant difference between samples collected in dry season and those collected in rainy seasons. Taken together, this study demonstrated that the nested RT-PCR method was superior to microscopy for detection of P. vivax mature gametocytes in patients’ blood samples that could be efficiently stored either on filter paper or RNA preservative and that a high prevalence of submicroscopic P. vivax gametocytemia occurred in both low (dry season) and high (rainy season) transmission seasons in an endemic area of Thailand.